Development of the complex description of business processes in the organization - Захарченко, Вікторія Петрівна; Марченко, Анна Вікторівна; Неня, Віктор Григорович; Окопний, Руслан Петрович (Technology audit and production reserves, 2016)
The analysis of graphic and formal methods and techniques for description of business processes is conducted. It is revealed the lack of a common approach to information presenting of all business processes lifecycle. The proposed information technology for combining different descriptions in a unit and methods of transition from one description mode to another is not yet possible to implement without loss of information and ensuring all participants of business processes lifecycle in a single conceptual framework. A comprehensive interrelated description of all aspects of business processes is proposed. This description appears in text, image, formal and algorithmic species as different forms of a single process models, which complement each other and can best solve various problems. This approach provides a convenient way of describing the process by specialists of different levels: from the head in the conceptual process design (planning) to direct performer during his work in securing the conditions for monitoring and control process. The basis for the creation of an information technology and software environment for planning, modeling, analysis, support and performance management of business processes is developed.